Genetic testing, a challenge to kidney biopsy? A case report: Genetic testing in persistent proteinuria - Simsek, Behcet (Journal of Surgery and Medicine, 2024)
The field of genetic testing has experienced significant growth in medical practice since 1956, when the first genetic analysis was introduced. Persistent proteinuria has long been considered a strong risk factor for the progression of chronic renal failure, though, paradoxically, it can also be a benign process, as seen in individuals with mutations in the cubilin (CUBN) protein, specifically the C-terminal. CUBN is a peripheral protein that plays a crucial role in the receptor-mediated endocytotic reabsorption of albumin in the proximal tubule. In the past, there have been misinterpretations of CUBN variants with isolated proteinuria as glomerular injury, leading to unnecessary kidney biopsies and ineffective treatments. This paper discusses two siblings with a homozygous variant of (p.Tyr3018Ser) in the C-terminal of the CUBN protein, inherited from both heterozygous carrier parents. This case presents an opportunity to question our typical approach to proteinuria in an effort to avoid unnecessary kidney biopsies and the subsequent side effects of treatments, particularly for those with proteinuria.